Obesity study in Malaysian Malays with focus on candidate genes and biomarkers / Yamunah Devi Apalasamy - Apalasamy, Yamunah Devi (2012)
Obesity is in rising prevalence globally and it has been associated with high mortality rate and other comorbidities. Obesity is a highly heritable disorder but genes responsible for hereditary variations remain to be largely elusive. Recent findings have shown that single nucleotide polymorphisms (SNPs) in the following genes predispose to the increased risk of obesity and obesity-related traits: leptin (LEP), melanocortin-4 receptor (MC4R), β2-adrenoceptor (ADRB2), insulin-induced gene 2 (INSIG2), syndecan 3 (SDC3), fat mass and obesity associated (FTO), resistin (RETN) and adiponectin (ADIPOQ). Biomarkers such as adiponectin, leptin and resistin have been shown to be tightly linked to obesity related metabolic pathways. This study was aimed to investigate association between obesity and obesity-related parameters such as Body Mass Index (BMI), body weight, height, waist circumference, hip circumference, waist hip ratio, blood pressure, cholesterol and lipid parameters with SNPs and biomarker levels. A total of 672 Malaysian Malay subjects were studied. Genotyping was carried out using two methods, namely, Real-Time PCR Taqman® SNP genotyping assays and also Sequenom MassARRAY. Data were analyzed using SPSS 16.0 statistical software and Haploview version 4.2. After adjustment with age, gender, related biomarker levels and Bonferroni correction, the present study exhibited significant associations between FTO rs17817288 with LDL-Cholesterol; MC4R rs571312 with logBMI and systolic blood pressure; MC4R rs2229616 SNP with total cholesterol; ADRB2 rs1042714 SNP with diastolic blood pressure, RETN rs3219175 and rs34861192 SNPs with weight and log-resistin levels. Strong linkage disequilibrium (LD) pattern was observed in resistin, FTO, ADRB2 and LEP gene. There is low LD in ADIPOQ and MC4R gene regions in this population. The leptin haplotype designated as GCCGGAA in this study, was associated with obesity in Malaysian Malays. This study suggests that the variants of the MC4R, ADRB2, LEP, RETN and FTO genes may have important roles for the development of obesity-related metabolic traits in the Malaysian Malay population. Levels of adiponectin and leptin in plasma were linked to obesity and metabolic abnormalities in Malaysian Malays but resistin appeared have less effect on obesity and metabolic abnormalities.